PENGARUH DIGITAL EKONOMI TERHADAP PERTUMBUHAN EKONOMI DI NEGARA BERKEMBANG - Rifa’i, M. Anwar; Arifin, Nandang Syamsul (Jurnal Istiqro, 2025)
The digital economy has become a key factor influencing global economic growth, particularly in developing countries. Enhanced access to digital technology offers these countries opportunities to increase productivity and competitiveness in the global market. This study aims to analyze the impact of the digital economy on economic growth in developing countries, focusing on digital infrastructure, contributions to Gross Domestic Product (GDP), job creation, and the challenges faced. This research employs a literature review method, analyzing seven scholarly articles on the digital economy to identify major trends and causality patterns. The findings indicate that the digital economy significantly contributes to GDP, boosts productivity, and expands market access for small and medium enterprises (SMEs). Adequate digital infrastructure and supportive policies are essential to maximize the benefits of the digital economy. However, this study also identifies challenges such as the digital divide and cybersecurity risks, which may hinder equitable benefit distribution. The implications highlight the importance of digital infrastructure investments and inclusive policies to support a sustainable digital economy in developing countries.